Bacteriophage therapy created the necessary conditions for successful antibiotic suppression in a periprosthetic hip joint infection: a Case Report - Wahl, Peter; Schläppi, Michel; Loganathan, Archana; Uçkay, Ilker; Hodel, Sandro; Fritz, Benjamin; Scheidegger, Jens; Djebara, Sarah; Leitner, Lorenz; McCallin, Shawna (Frontiers in Medicine, 2025)
IntroductionTreatment failure remains an issue in periprosthetic joint infection (PJI). Bacteriophages offer new treatment options. However, there is still a lack of evidence to better define their usefulness and administration. We report a case in which antibiotic suppression was successful only after administration of bacteriophages.Case descriptionAntibiotic suppression was the only option for a 94-year-old male with methicillin-resistant Staphylococcus aureus (MRSA) PJI of the hip and of the knee. As the hip PJI could not be suppressed adequately, bacteriophages were administered locally and systemically together with daptomycin. This combined approach led to sufficient clinical improvement for further oral antibiotic suppression, although without infection eradication.ConclusionThe administration of bacteriophages may be a valuable, less-invasive adjunct therapy to successfully suppress PJI. Bacteriophage selection, preparation and administration, however, remains associated with administrative obstacles, greatly limiting availability and practicability. Nevertheless, research and developments in this domain should be pursued, particularly considering issues with future antibiotic limitations and cost associated with treatment failure in PJI.